Pengaruh Service Excellent Unit Ground Handling Kokapura Terhadap Kepuasan Penumpang di Bandar Udara Internasional Jendral Ahmad Yani Semarang - Iklima Pingky Afsherina; Hodi (MES Bogor, 2024)
The main objectives of this research are as follows: 1) evaluate how much influence the excellent service of the Kokapura ground handling unit at Ahmad Yani International Airport Semarang has on passenger satisfaction; and 2) measure how much influence the excellent service of the Kokapura ground handling unit at Ahmad Yani International Airport Semarang has on passenger satisfaction. This research used a quantitative approach and collected 100 respondents who were passengers at Ahmad Yani International Airport, Semarang. The purposive sampling method was used for non-probability sampling. Certain criteria were used to select respondents. The results of statistical data analysis show that each statement in this study is valid and the variables are reliable. Hypothesis testing produces a significance value of 0.000 < 0.05 which indicates rejection of H0, and a calculated t value of 4.155 > t table value of 1.660 which indicates acceptance of Ha. The results of the regression test show that there is a positive and significant influence of 39.4%. In conclusion, the ground handling unit excellent service variable (X) has a significant influence on the passenger satisfaction variable (Y). In other words, this research proves that the excellent service of the Kokapura ground handling unit has a positive and significant effect on the level of passenger satisfaction at Ahmad Yani International Airport, Semarang. influence of 39.4%.